Strengthening the WAEMU Regional Fiscal Framework - David, Antonio (IMF Working Papers; Working Paper, 2022)
This paper assesses the adequacy and effectiveness of the WAEMU fiscal framework along three pillars that have proven to effectively support fiscal discipline in monetary unions-common fiscal rules (including adequacy of numerical ceilings as well as elements of design and enforcement), shared public financial management systems, and coordination mechanisms for decentralized fiscal policies. We undertake a calibration of regional debt and fiscal deficit ceilings taking into account different macroeconomic tradeoffs and risks and conclude that numerical ceilings that prevailed before the suspension of the fiscal rules remain adequate and strike the right balance between growth and fiscal sustainability. The paper also proposes reform options to strengthen the WAEMU regional fiscal surveillance framework, with a view to more effectively supporting fiscal discipline.